2018
DOI: 10.3857/roj.2018.00290
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induced secondary malignancies: a review article

Abstract: Radiation-induced second malignancies (RISM) is one of the important late side effects of radiation therapy and has an impact on optimal treatment decision-making. Many factors contribute to the development of RISM such as age at radiation, dose and volume of irradiated area, type of irradiated organ and tissue, radiation technique and individual and family history of cancer. Exact mechanism of RISM is unknown. But nowadays, it is a growing concern in oncology because of the increased number of cancer survivor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
156
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(189 citation statements)
references
References 70 publications
0
156
0
4
Order By: Relevance
“…Of these techniques, IMRT is a relatively new technique with the benefit of uniform dose distribution . However, it has the disadvantage of a larger low‐dose area, which has the possibility of increasing the risk of contralateral breast cancer or a secondary cancer . Another technique proposed to protect OAR is proton therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these techniques, IMRT is a relatively new technique with the benefit of uniform dose distribution . However, it has the disadvantage of a larger low‐dose area, which has the possibility of increasing the risk of contralateral breast cancer or a secondary cancer . Another technique proposed to protect OAR is proton therapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, it has the disadvantage of a larger low-dose area, which has the possibility of increasing the risk of contralateral breast cancer or a secondary cancer. 7 Another technique proposed to protect OAR is proton therapy. However, the number of clinics with proton therapy is limited and its current costeffectiveness has been reported to be inappropriate for use in breast cancer patients.…”
Section: Re Sultsmentioning
confidence: 99%
“…One of the important challenges to address during breast RT is secondary cancer risk. Various reports have shown that increased low doses may increase the risk of secondary malignancy development . The move from three‐dimensional conformal RT to intensity‐modulated techniques involves more fields, and the dose‐volume histograms show that, as a consequence, a larger volume of normal tissue is exposed to lower doses.…”
Section: Discussionmentioning
confidence: 99%
“…However, TBI can also cause severe long-term damage to several organs, such as the lung, trachea and mouth (radiation-induced pneumonitis, fibrosis, oral mucositis) (Marks et al, 2003;Mehta, 2005), reproductive system (radiation-induced infertility) (Ogilvy-Stuart and Shalet, 1993), liver (radiation-induced liver disease) (Kim and Jung, 2017), gastro-intestinal tract (radiation-induced gastric mucositis, radiation-induced gastro intestinal syndrome) (Francois et al, 2013;Olcina and Giaccia, 2016) or kidney (radiation-induced nephropathy) (Cohen, 2000;Cohen and Robbins, 2003). Furthermore, TBI can also initiate secondary malignancies (Dracham et al, 2018).…”
Section: Impact Of Induced Deletion Of Bcl-xl In Adult Micementioning
confidence: 99%